Threats and challenges in the control of quarantine pathogens in the state of Roraima Brazil - Bernardo de Almeida Halfeld-Vieira; Daniel Augusto Schurt; Rosianne Nara Thomé Barbosa; Kátia de Lima Nechet (Agro@mbiente On-line, 2022)
Plant diseases can negatively impact the production and sale of agricultural crops in a given region. Because it is a border state, Roraima is a potential entry route of quarantine pathogens that can threaten Brazilian agriculture. Constant health surveillance is an essential tool to mitigate the risks of the introduction and spread of important pathogens. In order to avoid or reduce the negative impacts caused by diseases resulting from the introduction or occurrence of a pathogen, a well-structured phytosanitary inspection program and technical guidelines for producers are necessary. The combined efforts of research institutions and state agencies aim to reduce production losses caused by diseases. Thus, the objective of this review is to address the main threats and challenges in controlling quarantine pests in the state of Roraima based on the experience of research and extension institutions in monitoring, pest detection and mitigation strategies. In this respect, contextualizing the events discussed may contribute to guiding plant defense measures, thus mitigating the risks of quarantine pathogen introduction and spread in Roraima.